Psychometric properties of the Fibromyalgia Survey Questionnaire (FSQ) in Chilean women with fibromyalgia. - Aguirre Cárdenas, Carla; Oñederra, María Cecilia; Esparza Benavente, Catalina; Durán, Josefina; González Tugas, Matías; Gómez-Pérez, Lidia (Lippincott, 2021)
Objective: to evaluate the psychometric properties of the Chilean version of the FSQ. Methods: Women with fibromyalgia (FM, n = 214), women with rheumatoid arthritis (RA, n = 97), and women without chronic pain (attended at the Gynecologist, G, n = 117) from the Red Salud UC-Christus (Santiago, Chile) participated. Women with FM completed the Fibromyalgia Survey Questionnaire ; Fibromyalgia Impact Questionnaire Revised ; Numerical Pain Rating Scale; Pain Catastrophizing Scale; Pain Vigilance and Awareness Questionnaire; Patient Health Questionnaire-15; and Short-Form Health Survey . Two weeks later, they completed the FSQ again by phone (n=120). Results: the FSQ total scale showed excellent to good internal consistency at T1 ( α = .91, ω = .91) and T2 ( α = .78, ω = .78) and good test-retest reliability (ICC=.79; 95%CI: .72-.85). It showed medium to large correlations with the other measures. Discriminant analysis between FM group and Control group (RA and G) revealed that the FSQ total scale reached a classification accuracy of 81.3%. ROC curve (AAUC= .88; 95%CI: .85-.92) showed that the best FSQ cutoff was 17, resulting in sensitivity 89% (95%CI:.84-.93) and specificity 75% (95%CI:.69-.80). Considering the FM diagnosis performed by a rheumatologist as the gold standard, sensitivity and specificity of the modified 2010 ACR preliminary criteria for FM were 92.8% (95%CI:.88-.96) and 63.4% (95%CI:.57-.70), respectively. Conclusion: the Chilean version of the FSQ presents good psychometric properties and is a useful tool in clinical settings to assist in FM diagnosis and symptomatology assessment. A cutoff score of ≥ 17 appears to be the most appropriated for Chilean population.
https://openpolicyfinder.jisc.ac.uk/id/publication/8819
Keywords: Fibromialgia; Aparato locomotor; Dolor; Mujeres; Psicometría; Fibromyalgia; Illness index severity; Musculoskeletal pain; Outcome assessment